Slave, Warrior, Queen (Of Crowns and Glory--Book 1) - Morgan, Rice (Lukeman Literary, 2016)
"Morgan Rice has come up with what promises to be another brilliant series, immersing us in a fantasy of valor, honor, courage, magic and faith in your destiny. Morgan has managed again to produce a strong set of characters that make us cheer for them on every page....Recommended for the permanent library of all readers that love a well-written fantasy." --Books and Movie Reviews, Roberto Mattos (regarding Rise of the Dragons) From #1 Bestselling author Morgan Rice comes a sweeping new fantasy series. 17 year old Ceres, a beautiful, poor girl in the Empire city of Delos, lives the harsh and unforgiving life of a commoner. By day she delivers her father's forged weapons to the palace training grounds, and by night she secretly trains with them, yearning to be a warrior in a land where girls are forbidden to fight. With her pending sale to slavehood, she is desperate. 18 year old Prince Thanos despises everything his royal family stands for. He abhors their harsh treatment of the masses, especially the brutal competition-The Killings-that lies at the heart of the city. He yearns to break free from the restraints of his upbringing, yet he, a fine warrior, sees no way out. When Ceres stuns the court with her hidden powers, she finds herself wrongfully imprisoned, doomed to an even worse life than she could imagine. Thanos, smitten, must choose if he will risk it all for her. Yet, thrust into a world of duplicity and deadly secrets, Ceres quickly learns there are those who rule, and those who are their pawns. And that sometimes, being chosen is the worst that can happen. SLAVE, WARRIOR, QUEEN tells an epic tale of tragic love, vengeance, betrayal, ambition, and destiny. Filled with unforgettable characters and heart-pounding action, it transports us into a world we will never forget, and makes us fall in love with fantasy all over again. Book #2 in OF CROWNS AND GLORY will be released soon!
Keywords: Sci-fi, fantasy; Dobrodružství, napětí, fantasy